Sugar concentrations and expression of SUTs suggest active phloem loading in tall trees of Fagus sylvatica and Quercus robur - Miehe, Wiebke; Czempik, Laura; Klebl, Franz; Lohaus, Gertrud (Tree Physiology, 2023)
Phloem loading and sugar distribution are key steps for carbon partitioning in herbaceous and woody species. Although the phloem loading mechanisms in herbs are well studied, less is known for trees. It was shown for saplings of Fagus sylvatica L. and Quercus robur L. that the sucrose concentration in the phloem sap was higher than in the mesophyll cells, which suggests that phloem loading of sucrose involves active steps. However, the question remains whether this also applies for tall trees. To approach this question, tissue-specific sugar and starch contents of small and tall trees of F. sylvatica and Q. robur as well as the sugar concentration in the subcellular compartments of mesophyll cells were examined. Moreover, sucrose uptake transporters (SUTs) were analyzed by heterology expression in yeast and the tissue-specific expressions of SUTs were investigated. Sugar content in leaves of the canopy (11 and 26 m height) was up to 25% higher compared with that of leaves of small trees of F. sylvatica and Q. robur (2 m height). The sucrose concentration in the cytosol of mesophyll cells from tall trees was between 120 and 240 mM and about 4- to 8-fold lower than the sucrose concentration in the phloem sap of saplings. The analyzed SUT sequences of both tree species cluster into three types, similar to SUTs from other plant species. Heterologous expression in yeast confirmed that all analyzed SUTs are functional sucrose transporters. Moreover, all SUTs were expressed in leaves, bark and wood of the canopy and the expression levels in small and tall trees were similar. The results show that the phloem loading in leaves of tall trees of F. sylvatica and Q. robur probably involves active steps, because there is an uphill concentration gradient for sucrose. SUTs may be involved in phloem loading.
CRIS-Team Scopus Importer:2023-06-02
Keywords: non-aqueous fractionation; subcellular metabolite concentration; sucrose transporter